Composition and Abundance of Habitat Plants Amorphophallus hewittii Alderw. in Mount Roban Forest, Singkawang City - Restu Dwi Candra; Irwan Lovadi; Siti Ifadatin; Dwi Gusmalawati (Jurnal Biologi Tropis, 2026)
Amorphophallus hewittii is a characteristic species of Southeast Asian tropical forests that depends on its habitat conditions. This study aims to identify the composition of plant species forming the habitat of A. hewittii in Gunung Roban Forest, East Singkawang, and analyze its community structure based on abundance, Importance Value Index (IVI), and species diversity. Data collection was conducted in October 2023 using a purposive sampling method with a stratified plot design. A total of 18 species with 247 individuals were found, dominated by Durio zibethinus (41 individuals), Hevea brasiliensis (39 individuals), and Caryota mitis (23 individuals), with the highest number of individuals in the western part (70 individuals) and the lowest in the northern part (42 individuals). D. zibethinus had the highest IVI at the tree and seedling levels, while Artocarpus altilis was dominant at the sapling level and H. brasiliensis at the pole level. The Shannon-Wiener Diversity Index indicated a moderate level of diversity. The average air temperature in the habitat ranged from 26–29°C, soil temperature from 25–28°C, air humidity from 28–83%, light intensity from 423–660 Cd, and soil pH from 6.0–7.0. The dominance of commercial species reflects human intervention, yet the moderate diversity level suggests that the ecosystem remains relatively stable and productive.